PENGOLAHAN CAKE BERBASIS PANGAN LOKAL SAGU PADA JEMAAT BUKIT SION GUNUNG NONA, KOTA AMBON - Mailoa, Meitycorfrida; H. Tulalessy, Abraham (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2022)
The goal of this community service project was to train ecclesiastical organizations in Gunung Nona, Ambon City. The community members who are members of the Bukit Zaitun Congregation’s men’s and women’s service centers are the target audience for this activity. Teaching and training methods are employed. Through this training program, the community is taught how to turn sago flour into lemon-flavored cakes by combining it with a variety of other food additives, called “lemon sago cake” (Cake Sag’L). The community is also informed about the health benefits of sago. The goal of the training activity is to improve science and technology as well as skills so that the community can use local sago food resources to create useful and innovative products that consumer will accept.